Abrasion resistance of direct and indirect resins as a function of a sealant veneer - Caneppele, Taciana Marco Ferraz; Rocha, Daniel Maranha; Araujo, Maria Amelia Máximo; Valera, Màrcia Carneiro; Marocho, Susana MarIa Salazar [UNESP] (Indian Journal Of Dental Research : Official Publication Of Indian Society For Dental Research, 2014)
Abrasive wear is one of the most common type of wear that not only affect teeth, as also dental restorations. Thus to investigate one of the etiological factors as tooth brushing procedure is clinical relevant in order to select the best material combination that may prevent damage of resin dental restoration's abrasion. This study evaluated the influence of tooth brushing on mass loss and surface roughness of direct Venus (Vs) and indirect Signum (Sg) resin composites, with and without a surface sealant, Fortify (F). Twenty-four specimens were prepared with each resin composite, using their proprietary curing units, according to manufacturer's instructions. All the specimens were polished and ultrasonically cleaned in distilled water for 5 minutes. Half of the specimens of each resin (n = 12) were covered with F (Vs F and Sg F ), except for the control (C) specimens (Vs C and Sg C ), which were not sealed. Mass loss (ML) as well as surface roughness (Ra ) was measured for all the specimens. Then, the specimens were subjected to toothbrush-dentifrice abrasion, using a testing machine for 67.000 brushing strokes, in an abrasive slurry. After brushing simulation, the specimens were removed from the holder, rinsed thoroughly and blot dried with soft absorbent paper. The abrasion of the material was quantitatively determined with final measurements of ML and surface roughness, using the method described above. ML data were analyzed by two-way analysis of variance (ANOVA) and the analysis indicated that resin composites were not statistically different; however, the specimens sealed with F showed higher ML. Ra mean values of the groups Vs F and Sg F significantly increased. Tooth brushing affects mainly the roughness of the direct and indirect resin composites veneered with a sealant.
Keywords: Brushing abrasion; composite resins; sealant